A prospective study investigating the role of respiratory viral infections in Sudden Unexpected Death in Infancy (SUDI) at Tygerberg Medico-legal Mortuary - Ferreira, Janca (Stellenbosch : Stellenbosch University., 2020)
Thesis (MSc)--Stellenbosch University, 2020.